PLATE MOTION ON EUROPA AND NONRIGID BEHAVIOR OF THE ICY LITHOSPHERE: THE CASTALIA MACULA REGION - Patterson G.W.; Head J.W.; Pappalardo R.T. (My University, 2006)
We have developed a generalized quantitative technique for determining the finite pole of rotation between two rigid plates and use it to critically examine differing reconstructions of a region surrounding a prominent dark spot on Europa, Castalia Macula. This region is located near the equator of Europa's trailing hemisphere and has been suggested as a site where crustal convergence may have occurred. Previous reconstructions of the region have indicated that a ridge set and/or a band-like complex that define a collection of tectonic plates in the region accommodated surface contraction. However, a critical examination of the differences between these reconstructions has been complicated by the lack of a finite pole of rotation for the plates involved in either reconstruction. We have applied our modeling technique, coupled with a detailed examination of the morphology and cross-cutting relationships involving this ridge set and band-like complex, to determine if a unique reconstruction exists for several tectonic plates in this region. The cross-cutting relationships involving the ridge set also allow us to test the general assumption that plates behave rigidly on Europa. Assuming rigid behavior, our results suggest that a unique reconstruction does exist, indicating the ridge set accommodated surface contraction. However, analysis performed to test the assumption of plate rigidity indicates that one or more of the plates in the region did not behave rigidly. This does not rule out surface contraction along the ridge set but does indicate that a component of nonrigid behavior must be considered. © 2006 Elsevier Ltd. All rights reserved.
Keywords: CASTALIA MACULA; COMPRESSION; EUROPA; INVERSE MODELING; PLATE RIGIDITY